2002
DOI: 10.1063/1.1425407
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy surfaces for the photochemical reactions Ca*+H2→CaH+H

Abstract: A hierarchical family of global analytic Born-Oppenheimer potential energy surfaces for the H + H 2 reaction ranging in quality from double-zeta to the complete basis set limit Six 1 AЈ potential energy surfaces of the CaϩH 2 system have been calculated using an effective-core potential and a core-polarization potential for Ca. Large configuration interactions were performed to ensure accurate energies and wave functions. The 2 1 AЈ surface, made from Ca(4s3d, 1 D), has a very stable intermediate, and crosses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…15 Furthermore, the study on the Ca( 1 D) + H 2 reaction revealed that the reaction has a preference for a near C 2v collision configuration, 16 and the allocated proportions of product available energy for rotation, vibration, and translation are 0.36 ± 0.05, 0.28 ± 0.04, and 0.36 ± 0.05, respectively. 17 Theoretically, Lee et al 18 calculated six 1 A′ potential energy surfaces (PESs) of the Ca + H 2 reaction system by using an effective-core potential and a core-polarization potential for Ca. They also conducted a simple analysis of the possible reaction paths through the wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, the study on the Ca( 1 D) + H 2 reaction revealed that the reaction has a preference for a near C 2v collision configuration, 16 and the allocated proportions of product available energy for rotation, vibration, and translation are 0.36 ± 0.05, 0.28 ± 0.04, and 0.36 ± 0.05, respectively. 17 Theoretically, Lee et al 18 calculated six 1 A′ potential energy surfaces (PESs) of the Ca + H 2 reaction system by using an effective-core potential and a core-polarization potential for Ca. They also conducted a simple analysis of the possible reaction paths through the wave functions.…”
Section: Introductionmentioning
confidence: 99%